2015
DOI: 10.3109/0284186x.2015.1099731
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in second-line targeted therapy for metastatic clear-cell renal cell carcinoma after progression on an anti-vascular endothelial growth factor receptor tyrosine kinase inhibitor

Abstract: Submit your article to this journal Background: About 40% of metastatic clear-cell renal cell carcinoma (m-ccRCC) patients receive a second-line targeted therapy after failure of anti-vascular endothelial growth factor receptor tyrosine kinase inhibitors (anti-VEGFR-TKI). Efficacy of second-line therapy is usually limited and prognostic and predictive factors at the start of second-line therapy are lacking. To identify the subgroup of patients that will benefit from such treatment remains a challenge. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
9
1
Order By: Relevance
“…In this series, the median OS in the 271 patients included in this study was 24.8 months, which seems to be comparable or even superior to those in previous studies showing the prognosis of mRCC patients treated with second-line targeted agents [24]. Moreover, this study showed for the first time that the degree of ETS under second-line targeted therapy was proportional to OS among the four subgroups; that is, the median OS stratified according to the degree of ETS, as described above, was 45.8, 30.9, 22.1 and 14.2 months, respectively.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In this series, the median OS in the 271 patients included in this study was 24.8 months, which seems to be comparable or even superior to those in previous studies showing the prognosis of mRCC patients treated with second-line targeted agents [24]. Moreover, this study showed for the first time that the degree of ETS under second-line targeted therapy was proportional to OS among the four subgroups; that is, the median OS stratified according to the degree of ETS, as described above, was 45.8, 30.9, 22.1 and 14.2 months, respectively.…”
Section: Discussionsupporting
confidence: 78%
“…TKIs vs. mTOR inhibitors) failed to show independent impact on OS in the 271 patients. Despite limited findings regarding the prognostic factors in mRCC patients treated with second-line agents, currently available data suggest that traditional prognostic parameters in patients treated with first-line targeted agents could be applied to those receiving second-line therapy [24]. In fact, Ko et al recently reported that the IMDC prognostic model can be applied to mRCC patients receiving second-line targeted therapy in addition to previously validated populations undergoing first-line targeted therapy [25].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The study of Sacré et al (15) identified grading to be a prognostic factor at the start of second-line therapy. To our knowledge, there is no study so far that has identified pretreatment tumor grade as the predictor of eligibility to receive second-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although some other studies were reported that non-corrected and albumin corrected that total calcium levels weak predictors of calcium levels in CKD subjects. 8 Hence the present study compare the values of Ionized calcium along with Total and Albumin corrected calcium levels with CKD subjects.…”
Section: Introductionmentioning
confidence: 99%